A dynamic condensation method with free interface substructuring. (15th August 2019) - Kim, Jeong-Ho; Boo, Seung-Hwan; Lee, Phill-Seung
Highlights: A free-interface based dynamic condensation method is newly developed. In the formulation, substructural FE models are fully decoupled. Non-matching mesh and complicated substructural interfaces can be modeled. Accuracy, computational efficiency and modeling ability are demonstrated. Abstract: In this paper, a novel dynamic condensation method is proposed with free interface substructuring, in which the substructures are completely decoupled. The substructures are independently defined and the substructural finite element (FE) models are individually reduced by adopting the improved reduced system (IRS) method. The reduced mass and stiffness matrices of substructures are assembled using a Lagrange multiplier vector, leading to the final reduced model. Using the proposed method, each of the substructural FE models can be reduced in parallel without coupling among the neighboring substructures. Thus, the method can be applied with ease to substructures connected through non-matching meshes. Moreover, complicated substructural interfaces can be accommodated when employing this method. The formulation of the proposed method is presented in detail, and its accuracy, computational efficiency, and modeling ability are investigated using several demonstrative engineering problems.